960 views
1 vote
Send it quick guys...

Send it quick guys...-example-1
User Asaveljevs
by
5.0k points

1 Answer

2 votes

Answer:

194

Explanation:

Recall 2 rules to solve this easily:

1.
(a+b)^2=a^2+2ab+b^2

2.
(a-b)^2=a^2-2ab+b^2

Now, if we let a = 7 and
b=4√(3), we can say the problem is basically of the form:


(a+b)^2 + (a-b)^2

This can be simplified using the rules:


(a+b)^2 + (a-b)^2\\a^2+2ab+b^2+a^2-2ab+b^2\\2a^2+2b^2

Now we can plug the values of a and b we initially thought of (remember though
√(x) √(x) =x):


2a^2+2b^2\\2(7)^2+2(4√(3))^2\\ 2(49)+2(4√(3))(4√(3))\\98+2(4)(4)(√(3) )(√(3) )\\98+2(4)(4)(3)\\98+96 \\194

194 is the final answer.

User Jake Thompson
by
5.5k points